2022
DOI: 10.1111/1750-3841.16350
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of pulsed electric field and osmotic dehydration pretreatments on mass transfer and quality of air‐dried pumpkin

Abstract: Pulsed electric field (PEF) and osmotic dehydration (OD) pretreatment can accelerate the time-consuming drying process and minimize its high energy demands. The effect of PEF and OD pre-processing conditions and osmotic solution composition on mass transfer kinetics (water loss, solid gain, water activity) and quality properties (color, texture, total sensory quality) during OD and subsequent air-drying (AD) of pumpkin was studied. Application of PEF (2.0 kV/cm-1500 pulses) significantly enhanced mass transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…After 2 h of dehydration, the material previously treated with a PEF was characterized by a lower parameter compared to the material subjected to the osmotic dehydration process alone, while strawberries treated with ultrasound had higher ∆E values, but they were not statistically significant. Paraskevopoulou et al [60] found no significant differences in brightness (L*) between the fresh, PEF-pretreated, and osmotic dehydrated samples. Other studies have shown that a PEF can retain its color by releasing the intercellular content depending on the initial characteristics of the raw material, cell membrane permeability, and process conditions [60].…”
Section: The Influence Of Us or Pef Pretreatment On The Physical Prop...mentioning
confidence: 94%
See 2 more Smart Citations
“…After 2 h of dehydration, the material previously treated with a PEF was characterized by a lower parameter compared to the material subjected to the osmotic dehydration process alone, while strawberries treated with ultrasound had higher ∆E values, but they were not statistically significant. Paraskevopoulou et al [60] found no significant differences in brightness (L*) between the fresh, PEF-pretreated, and osmotic dehydrated samples. Other studies have shown that a PEF can retain its color by releasing the intercellular content depending on the initial characteristics of the raw material, cell membrane permeability, and process conditions [60].…”
Section: The Influence Of Us or Pef Pretreatment On The Physical Prop...mentioning
confidence: 94%
“…Paraskevopoulou et al [60] found no significant differences in brightness (L*) between the fresh, PEF-pretreated, and osmotic dehydrated samples. Other studies have shown that a PEF can retain its color by releasing the intercellular content depending on the initial characteristics of the raw material, cell membrane permeability, and process conditions [60]. In turn, research by Tylewicz et al [56] showed that the initial PEF treatment on the osmotic dehydrated of strawberries led to an increase in the L* value compared to the untreated strawberries.…”
Section: The Influence Of Us or Pef Pretreatment On The Physical Prop...mentioning
confidence: 94%
See 1 more Smart Citation